Kusaiean-English Dictionary - Lee, Kee-Dong (University of Hawai'i Press, 2023)
Kusaie is a small island in the middle of the Pacific Ocean, lying roughly midway between Pohnpei and the Marshalls. Its language is distinct from those of the other island groups of Micronesia, though it has many cognates with Marshallese. Designed to be a companion volume to the author's Kusaiean reference grammar, this dictionary will be of use to anyone wanting to learn the Kusaiean language or to linguists involved in comparative and historical studies of Austronesian linguistics.